Kumar & Clark's cases in clinical medicine - Kumar, Parveen J. (Parveen June); Clark, Michael L.eeditor (Elsevier, 2021)
"This thoroughly updated new edition covers more than 200 cases presenting with acute symptoms in the hospital, everything from shingles and breathlessness to chest pain, acute coronary syndromes, poisoning, renal failure and stroke. The authors give clear and concise advice on immediate and further management, management of complications, differential diagnoses, history-taking, tips and pitfalls, alerts, investigations, and prioritization."